Capacitive/inductive compensation factor in coupled lines wilkinson power divider design. Issue 12 (22nd September 2016) - Wang, Xiaolong; Ohira, Masataka; Ma, Zhewang; Sakagami, Iwata; Mase, Atsushi; Yoshikawa, Masayuki
ABSTRACT: In this article, two coupled line sections are taken place transmission lines for miniaturization in Wilkinson power divider. A general compensation factor is shunted in the middle of two coupled line sections to compensate the different input impedances between even‐ and odd‐mode, where, the factor could be capacitive or inductive reactance, and its value is determined by effective dielectric constants of substrate, coupling strength and its physical lengths of two coupled line sections. Compared with the function of compensated capacitor, the similar results are newly summarized in this article: compensated inductor could also be used to compensate different characteristic impedances in stripline structure (homogeneous medium), and compensate the difference of phase velocities microstrip line structure (inhomogeneous medium). Design charts and calculated bandwidths are discussed for both different structures. One experimental circuit was fabricated in microstrip line structure, and the measurement results showed good agreement with theoretical results © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2940–2944, 2016